Socialization on the utilization of household organic waste as liquid organic fertilizer in vegetable cultivation - Rina Ekawati; Anna Kusumawati; Lestari Hetalesi Saputri; Pantjasiwi Veni Rahayu Ingesti; Luci Paonganan (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
Waste or organic waste from households can be converted into liquid organic fertilizer (POC) because organic waste contains nutrients that can be used as fertilizer. Waste becomes a problem not only in urban areas but also in rural areas because the population is increasing, so that waste production is also more. Household waste that is generated every day can be used as fertilizer by composting, but its utilization is not optimal. The socialization activity aims to provide education and increase insight to the community into the use of household organic waste. The community is given knowledge about the importance of utilizing household organic waste, how to manage household organic waste through the composting process, utilizing household organic waste as liquid organic fertilizer in cultivating vegetable crops, the benefits and cost-efficiency of organic vegetables for family self-sufficiency and organic vegetable business opportunities. The socialization involved 35 people, and the form of activity evaluation uses a questionnaire containing general characteristics of the respondent and selected questions. The results of the evaluation show that the age characteristics of the respondents are 50 - 59 years old, and the level of formal education is from Junior High School to Senior High School. On average, respondents already know and understand how to use household waste by composting a composter bucket (100%) as liquid organic fertilizer